Simultaneous Regulation of Solvation Shell and Oriented Deposition toward a Highly Reversible Fe Anode for All‐Iron Flow Batteries. Issue 49 (30th October 2022) - Song, Yuxi; Yan, Hui; Hao, Huanhuan; Liu, Zihe; Yan, Chuanwei; Tang, Ao
Abstract: Developing low‐cost all‐iron hybrid redox flow batteries (RFBs) presents a practical alternative to the high‐cost all‐vanadium RFBs and is deemed vital for grid‐scale energy storage applications. However, the intrinsically poor Fe anode reversibility associated with the deposition and dissolution of metallic iron greatly limits the cycling performance and long‐term stability of all‐iron hybrid RFBs. Herein, a highly reversible and dendrite‐free Fe anode is reported for all‐iron RFBs through regulation of polar solvent dimethyl sulfoxide (DMSO) on FeCl2 anolyte, which simultaneously reshapes Fe 2+ solvation structure and induces controllable oriented Fe deposition. Combining both experimental and theoretical analyses, the polar DMSO additives prove effective in replacing H2 O molecule from the primary solvation shell of Fe 2+ cation via the Fe 2+ ‐O (DMSO) bond and meanwhile induces a fine‐grained Fe nucleation on the preferred Fe (110) plane, which are responsible for the minimized hydrogen evolution and dendrite‐free Fe deposition that significantly enhance Fe anode reversibility. The all‐iron RFB based on the proposed FeCl2 ‐DMSO anolyte demonstrates an excellent combination of peak power density of 134 mW cm −2, high energy efficiency of 75% at 30 mA cm −2, and high capacity retention of 98.6% over 200 cycles, which presents the best performance of all‐iron RFBs among previously reported research. Abstract : A highly reversible Fe anode is realized for all‐iron redox flow batteries (RFBs) through regulation of polar solvent dimethyl sulfoxide on FeCl2 anolyte, which simultaneously reshapes Fe 2+ solvation structure and induces controllably oriented Fe deposition. Consequently, the all‐iron RFB demonstrates an excellent combination of peak power density, energy efficiency, and capacity retention, which presents the best performance among previously reported research.